Multiple primary lung cancer: updates and perspectives - Wang, Ziqi; Zhang, Quncheng; Wang, Chaoyang; Herth, Felix; Guo, Zhiping; Zhang, Xiaoju (International journal of cancer, 2024)
Management of multiple primary lung cancer (MPLC) remains challenging, partly due to its increasing incidence, especially with the significant rise in cases of multiple lung nodules caused by low-dose computed tomography screening. Moreover, the indefinite pathogenesis, diagnostic criteria, and treatment selection add to the complexity. In recent years, there have been continuous efforts to dissect the molecular characteristics of MPLC and explore new diagnostic approaches as well as treatment modalities, which will be reviewed here, with a focus on newly emerging evidence and future perspectives, hope to provide new insights into the management of MPLC and serve as inspiration for future research related to MPLC.
Gesehen am 08.11.2024